THE INFLUENCE OF E-COMMERCE, PRICE, CAPITAL, BUSINESS TRAINING, AND REGIONAL ORIGIN ON THE INCOME OF CULINARY MSMEs IN DENPASAR CITY - I Komang Aditya Pratama; Ni Putu Martini Dewi (Adisam Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs), particularly in the culinary sector, play a crucial role in supporting regional economic growth, especially in Denpasar City, which serves as the center of economic and tourism activities in Bali Province. The advancement of digital technology, urbanization, and shifting consumption patterns require MSME actors to adapt rapidly and innovatively in order to increase their business income. This study aims to examine the simultaneous and partial effects of e-commerce, pricing, capital, business training, and regional origin on the income of culinary MSMEs in Denpasar City. Data collection was conducted through questionnaires distributed to 100 culinary MSME business owners in Denpasar. This study employed a non-probability sampling method using accidental sampling as the sampling technique. The data were analyzed using multiple linear regression analysis. The findings reveal that, simultaneously, e-commerce, price, capital, business training, and regional origin have a significant effect on MSME income. Partially, the variables of e-commerce, price, capital, and business training have a positive and significant influence on MSME income. Culinary MSMEs originating from Denpasar City tend to have higher incomes compared to those from outside the city.